Human Agents, Contexts, and Institutional Change: The Decline of Family in the Leadership of Business Groups - Chung, Chi-Nien; Luo, Xiaowei (Organization Science, 2008)
This study examines the interaction between change-minded human agents and environmental and organizational contingencies to understand contested change in highly institutionalized practices. We propose a theory of how individuals, including those who are structurally highly embedded, can become change agents when confronted with amplified institutional contradictions. Using the empirical example of family presence in the leadership of Taiwanese business groups, we argue that despite the structural constraints on second-generation key leaders, these leaders are more likely to actualize their motivation to reduce family presence in the contexts of market-oriented transition and highly diversified business groups, and that key leaders with a management education from the United States are more likely to deviate from this institutionalized practice than are non-U.S.-educated key leaders, because they can transport ideas from different business models. A longitudinal analysis of the top 100 business groups in Taiwan between 1977 and 1998 largely supports our arguments. This study contributes to recent endeavors to understand antecedents to institutional change with an explicit focus on the interplay between agency and context, and to business-group research by examining the change of one foundational feature of the group form.